2006
DOI: 10.1039/b516202e
|View full text |Cite
|
Sign up to set email alerts
|

Are gas-phase models of interstellar chemistry tenable? The case of methanol

Abstract: We consider the case of methanol production in cold dark clouds, also known as quiescent cores, for which recent work shows that a purely gas-phase synthesis is unlikely to produce a sufficient amount to explain the observational fractional abundance of approximately 10(-9). Moreover, recent experiments appear to confirm a previous hypothesis that methanol can be formed on cold grain surfaces by the hydrogenation of CO via successive reactions with hydrogen atoms. In this paper we consider two ways of includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
145
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(148 citation statements)
references
References 31 publications
2
145
1
Order By: Relevance
“…Methanol has been observed in interstellar ices and has been proposed as a good starting point for the formation of more complex species (Ö berg et al 2009). The hypothesis that interstellar methanol forms in the solid phase has been recently supported by experimental and modeling work, showing that the gas-phase route via ion-neutral reactions is less efficient than previously assumed (Geppert et al 2005;Garrod et al 2006). However, the first studies on solid CO hydrogenation by two different groups yielded conflicting results: in one study (Hiraoka et al 2002) only the formation of H 2 CO was reported, whereas in the other study also CH 3 OH was observed (Watanabe and Kouchi 2002).…”
Section: Surface Formation Of Methanolmentioning
confidence: 81%
“…Methanol has been observed in interstellar ices and has been proposed as a good starting point for the formation of more complex species (Ö berg et al 2009). The hypothesis that interstellar methanol forms in the solid phase has been recently supported by experimental and modeling work, showing that the gas-phase route via ion-neutral reactions is less efficient than previously assumed (Geppert et al 2005;Garrod et al 2006). However, the first studies on solid CO hydrogenation by two different groups yielded conflicting results: in one study (Hiraoka et al 2002) only the formation of H 2 CO was reported, whereas in the other study also CH 3 OH was observed (Watanabe and Kouchi 2002).…”
Section: Surface Formation Of Methanolmentioning
confidence: 81%
“…Methanol is expected to form via successive hydrogenation of CO on the surface of dust grains and then partially released in the gas phase upon formation (i.e., part of the formation energy is used to evaporate, in a process called reactive desorption; Garrod et al 2006) and/or upon photo-desorption by UV photons produced by cosmic-ray impacts with H 2 molecules (Prasad & Tarafdar 1983). Evaporated methanol will then freeze-out onto dust grains in a time scale inversely proportional to the gas number density (∼10 9 /n H yr; van Dishoeck et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Garrod et al (2006) conclude that the production of methanol is carried out on the surfaces of dust grains followed by desorption into the gas. The X CH 3 OH values in G11.P11 could then be produced by desorption of icy mantles on the dust grains.…”
Section: Ch 3 Oh Abundancesmentioning
confidence: 99%